Російське православ'я та ідея соборності - Клименко, О. (Схід, 2009)
Стаття присвячена розгляду відображення в російській історії тих ідей та ідеалів, що
були вироблені в рамках православної церковної свідомості.
Такий розгляд є важливим як первинне освоєння руською думкою, первинна секуляризація теми, узятої до опрацювання. Ідеал "симфонії влади", запозичений від Візантії, розуміється як основа та початок, що направляє всі варіанти російських ідеологій: християнсь-
ко-імперської ідеї у вигляді теорії "Третього Риму", самодержавної ідеї Івана Грозного, основної монархії XVII ст. Абсолютизм Петра І та теорія "офіційної народності" відходять від
ідеалу "симфонії влади" та від соборної єдності, але сприйняття влади народом так і залишається в цілому обумовленим вищеназваними ідеями. Article is devoted consideration of expression in Russian history of those ideas and ideals which were mine-out
within the framework of orthodox church co nsciousness .
Such consideration is important as a primary mastering, primary secularizing of interesting us theme the Russian
idea. The ideal of "symphony of authorities", adopted from Byzantium, is understood as basis and sending beginning
of all variants of Russian ideologies: christian-imperial idea as a theory of "Third Rome", autocratic idea in the person
of Ivan Threatening, to the class monarchy of XVII age.
Absolutism of Peter I and theory of "official nationality" walk away from the ideal of "symphony of authorities" and
from cathedral unity, by him expressed (last, true, legalistically tries to set him), but perception of power so remains
people it is on the whole certain the ideas ad opted higher: autocracy an d class wi th the elements of messiah
consciousness.